ANALISIS KINERJA PEGAWAI BIDANG PENGENDALIAN DAN PENERTIBAN (DALTIB) PADA DINAS LALU LINTAS DAN ANGKUTAN JALAN DALAM MENGATASI KEMACETAN DI KOTA BOGOR - Dea Hilmiah Halawi; Rita Rahmawati; Euis Salbiah (Jurnal Governansi, 2016)
Traffic Jam is a major problem many cities in Indonesia, including in Bogor city. Traffic Jam in Bogor city  is almost equal to the capital city of Jakarta. There are many factors that caused traffic jam in Bogor. In addition to the number of population is increasing,  mobility of the population is also quite high. The purpose of this study was to determine employees performance of Department of Traffic and road transportation Bogor in handling of traffic jam. The method used in this research is survey method with quantitative approach. The results showed that the views of the dimensions of productivity, quality of service, responsiveness, responsibility, and accountability are very good category. Although the results of employee respondents considered that the assessment of employee performance has been very good, but in the view of the driver, passengers and road users were different. They noticed that traffic jam in Bogor City can not be addressed properly. Key words: Traffic Jam, Performance Employee, Service quality.